On the homogeneity of fluids forming bedding‐parallel veins. Issue 1 (6th May 2013) - Smith, A. P.; Fischer, M. P.; Evans, M. A.
Abstract A group of 400–500 m long, bedding‐parallel calcite veins are exposed in the central La Popa Basin of northeastern Mexico. These veins provide a unique opportunity to determine the kilometer‐scale fluid–rock system associated with bedding‐parallel vein formation, and to test for sampling bias in studies that often use one or two samples to constrain the characteristics of regional‐scale paleohydrogeological systems. We use fluid inclusion microthermometry in conjunction with measurements of δ13C, δ18O, and 87Sr/86Sr ratios to constrain the vein‐forming fluid temperatures, compositions and sources, and compare these values along and between the veins to establish the homogeneity of the vein‐forming fluids and fluid–rock system. The δ13C values of the veins are close to those of the host rock, and average – 3.96‰ (PDB). The δ18O values of the veins are typically 1‰ lower than those of the host rocks, and average – 9.54‰ (PDB). Fluid inclusion homogenization temperatures average 137°C and inclusion salinities are all <6 wt% NaCl equivalent. The 87Sr/86Sr ratios of the veins average 0.70731 and are substantially lower than the values expected for the host rock. Calculated fluid δ18O values range from 4 to 10‰ (SMOW). The isotopic and microthermometric data indicate the veins most likely formed at depths of 3–4 km when meteoric water mixed with upward migrating, warm basinal brines. Vein microstructures and field characteristics indicate they formed from multiple slip events that most likely were associated with transport of individual fluid pulses that migrated along bedding planes. The large‐scale homogeneity of vein geochemistry is remarkable and demonstrates that only one or two samples would be sufficient to accurately characterize the kilometer‐scale paleohydrogeological system for these veins.